Green Port Strategies in Developed Coastal Countries as Useful Lessons for the Path of Sustainable Development: A case study in Vietnam - Hoang Phuong Nguyen; Phuoc Quy Phong Nguyen; Thanh Phuong Nguyen (International Journal of Renewable Energy Development, 2022)
The global shipping industry has been contributing more than four-fifths of the volume of goods transported internationally. However, shipping is facing pressure from strict policies on combating climate change from the International Maritime Organization (IMO). Seaports are an essential component of shipping and are also having to change their development strategies to be more sustainable and smarter. The concept of a green port was born as an inevitable part of the green economic development path. Green port system development policies and strategies have been discussed and studied in recent literature reviews, and have revealed the limited reach of developing countries. This work focuses on evaluating successful green port policies and concepts in developed countries to highlight the distinctive features of green ports. Moreover, the experiences from the effective green port models of developed countries can be valuable lessons for developing countries like Vietnam. More interestingly, the core features of green ports, when piloted at several international ports in Vietnam, promote port efficiency and environmental friendliness. On the way to implementing the national green port strategy, Vietnam has been establishing legal and infrastructure corridors to realize the strategy of sustainable marine economic development by 2045.